PENERAPAN METODE OBSERVASI UNTUK MENINGKATKAN HASIL BELAJAR IPS DAN LITERASI SAINS - Wawahidah, Halimatu; Kurnia, Dadang; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
The outcome of learning that have not reached the maximum completeness criteria (KKM) for fourth grade students of SDN Mandalaherang II about the utilization of natural resources based on local conditioned needs to improve the learning. It is aimed to know the improvement of students’ science literacy and learning outcome of fourth grade students of SDN Mandalaherang II. The researcher used Kemmis and McTaggart’s design ‘Classroom Action Research’ (CAR) consists of planning, acting, observing, and reflecting. The instruments used in this research are observation sheet of teacher’s performance, activity sheet of students’ performance, students’ learning outcome, test result of science literacy application, teacher’s and students’ application, teacher’s interview guideline and questionnaire of students’ response to learning. The result of cycle I is 72.22%, it has increased to 88.88% in cycle II, and it has increased to 100% in cycle III. Students’ activity in cycle I reached 17.85%, it has increased to 71.42% in cycle II, and it has increased to 89.28% in cycle III. It can be concluded that observational method can improve students’ learning outcome and science literacy on material ‘utilization of biological natural resource based on local natural conditions’.